(3GdfXGe GdfbOj GdOhdj COhGJ bhGYO h BdjGJ JSjjQjI (B/s ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
(3GdfXGe GdfbOj GdOhdj hCOhGJg GdJSjjQjI , eGgjJg, eY fXGe GdbGYOI GdPgHjI, COhGJ hBdjGJ GdJMce hcPdc fXGe (Bbretton woods (3hfXGe GdJYhje, HGdGVGaI Gdi GdfXGe GdfbOj GdOhdj HYO CMOGK CReI (B2008 (3GdPj JVef GdGWGQ GdYGe HMce GdJYGed GdGbJUGOj eG Hjf Ohd GdYGde hJMOjO GdYhGed GdeDOjI Gdi GdCReGJ eY JcKja GdLghO GdOhdjI, hGdeHGOF GdCSGSjI dGUdGM GdCShGb GdeGdjI hGdGJaGb Ydi JWHjb eHGOF eTJQcI dg hGdJYGhf GdOhdj(B.s
(3eQGLY U(B.155- 174 (3edGMb U(B.175- 176s
Keywords: (3GdeGdjIs; (3GdfXGe GdfbOj GdOhdjs